THE RELATIONSHIP BETWEEN KNOWLEDGE AND ATTITUDE WITH EFFORT OF SCHISTOSOMIASIS PREVENTION BY COMMUNITY IN THE WORK AREA PUBLIC HEALTH CARE CENTER OF WUASA - Noviany Banne Rasiman (Berkala Kedokteran, 2022)
Abstract: Schistosomiasis is a disease caused by worm Schistosoma japonicum which requires an intermediate animal, namely a snail called Oncomelania Hupensis Lindoensis. In the work area Health Care Canter of Wuasa, the disease is still many cases, because most of the population are immigrants, they are open rice fields and plantations in the focus area of snail. The purpose was to determine the relationship between knowledge and attitudes with the effort of Schistosomiasis prevention by Community in the Public Health Care Center of Wuasa, North Lore District, Poso Regency. This type of research is analytic with cross sectional approach. The variables in this study are the knowledge and attitudes of the community with efforts to prevent Schistosomiasis. The types of data are primary and secondary. data collection using a questionnaire. Data analysis used univariate and bivariate analysis with Chi-square test. The population in this study were all people of North Lore District. Sampling using proportional random sampling technique with total 99 respondents. The results of the univariate analysis showed that 77.8% of respondents had good knowledge of schistosomiasis prevention efforts, 52.5% of respondents had good attitudes and 83.8% of respondents had quite good schistosomiasis prevention efforts. Bivariate analysis with Chi-square statistical test with 95% confidence level with a significance value of 0.05. The results showed that there was a relationship between knowledge and efforts to prevent Schistosomiasis with p-value = 0.000 (where p < 0.05) and there was a relationship between community attitudes and efforts to prevent Schistosomiasis disease with p-value = 0.003 (where p < 0.05). The conclusion of the study were there is a significant relationship between knowledge and attitudes of the community with efforts to prevent Schistosomiasis in the Public Health Care Center of Wuasa. Suggestions to the health workers in the work area of health care center to increase local community awareness in supporting the prevention of Schistosomiasis disease.Keywords: Knowledge; attitude; prevention; Schistosomiasis.